Dark matter halos in galaxies - Machado, Rubens (Cadernos de Astronomia, 2024)
Dark matter halos are essential for understanding the dynamics of galaxies. In this paper, we present the concept of rotation curve in an introductory manner to explain the need for dark matter in galaxies. Subsequently, we delve into a more detailed examination of the spatial distribution of dark matter, namely, its density profile. Finally, we place the dark matter halo in the context of the other components (stellar disk, bulge, and gas) to construct a compound dynamical model.
Keywords: astronomy; galaxies; dark matter